2016
DOI: 10.1016/j.crvi.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Tibetan fox (Vulpes ferrilata) and implications for the phylogeny of Canidae

Abstract: Canidae is a family of carnivores comprises about 36 extant species that have been defined as three distinct monophyletic groups based on multi-gene data sets. The Tibetan fox (Vulpes ferrilata) is a member of the family Canidae that is endemic to the Tibetan Plateau and has seldom been in the focus of phylogenetic analyses. To clarify the phylogenic relationship of V. ferrilata between other canids, we sequenced the mitochondrial genome and firstly attempted to clarify the relative phylogenetic position of V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Corsac fox (Vulpes corsac) is mainly lhabitated in Central Asia and is the smallest species among foxes (Zhao et al 2016b) (Zhao et al 2016a, b). Previous studies on corsac were mainly focused on their genetics and systematic taxonomy (Graphodatsky et al 2008;Zhao et al 2016a;Shang et al 2017), biochemistry, and physiology (I V et al 1900;Pozio et al 1992;Tang et al 2001;Kuzmin et al 2004;Botvinkin et al 2008;Odontsetseg et al 2009;Ito et al 2013), as well as ecological distribution (Mal'kova 2000;Tang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corsac fox (Vulpes corsac) is mainly lhabitated in Central Asia and is the smallest species among foxes (Zhao et al 2016b) (Zhao et al 2016a, b). Previous studies on corsac were mainly focused on their genetics and systematic taxonomy (Graphodatsky et al 2008;Zhao et al 2016a;Shang et al 2017), biochemistry, and physiology (I V et al 1900;Pozio et al 1992;Tang et al 2001;Kuzmin et al 2004;Botvinkin et al 2008;Odontsetseg et al 2009;Ito et al 2013), as well as ecological distribution (Mal'kova 2000;Tang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Corsac fox ( Vulpes corsac ) is mainly lhabitated in Central Asia and is the smallest species among foxes (Zhao et al . 2016b ) (Zhao et al . 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis showed that the genome structure is consistent with other Passeriformes species, which contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, 1 control region, and 1 extra pseudocontrol region. The structure of the mitogenome is a typical vertebrate mitochondrial gene arrangement (Boore 1999;Zhang et al 2016;Zhao et al 2016). Nine genes were encoded on the L-strand, including ND6 and 8 tRNA genes, and the remaining 28 genes were encoded on the H-strand.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…Sequence analysis showed that the genome structure is consistent with other Passeriformes species, which contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and 2 control regions. The structure of the mitogenome is a typical vertebrate mitochondrial gene arrangement (Boore 1999;Sun et al 2016;Zhao et al 2016).…”
mentioning
confidence: 99%